The river pollution claims problem - Yuzhi Yang; Erik Ansink (Tinbergen Institute, 2022)
We propose the river pollution claims problem to distribute a limited pollution budget among agents located along a river. A key distinction with the standard claims problem is that agents are ordered and they are given priority based on their location in this order instead of their identity. We propose two new axioms that are relevant in the context of river pollution and use these to characterize two priority rules. Our characterization results show that Consistency plays an important role since it makes sure that any asymmetric treatment will be transferred across problems.
Keywords: C71; D62; D63; Q25; 330; Claims Problem; River Pollution; Pollution Permits; Priority Rules